Genetic divergence analysis in groundnut (ArachishypogaeaL.) - K. Saritha; R. P. Vasanthi; M. Shanthi Priya and; P. Latha (Electronic Journal of Plant Breeding, 2018)
Genetic diversity among 32 genotypes of groundnut was estimated for six characters using Mahalanobis D2 statistic. The analysis of variance revealed significant differences among the genotypes for all characters. The characters, pod yield per plant, 100 seed weight and SLA at 60 DAS recorded moderate to high GCV, high heritability coupled with high genetic advance as percent of mean indicating that these traits were mainly under the influence of additive gene action and simple selection may be effective for improvement of these traits. Based on Tocher's method of clustering, 32 genotypes were grouped into eight clusters, of which cluster II was the largest containing 10 genotypes followed by cluster I with seven genotypes. The inter-cluster distance was maximum between cluster II and cluster VIII (2031.75) followed by cluster V and cluster VIII (1768.25) and cluster VII and VIII (1702.17). Considering the cluster distances and cluster means, crossing between the genotypes of cluster II and cluster VIII, and cluster VIII and cluster V is suggested in order to get transgressive segregants for yield and yield parameters.